A criação de vínculos sociais : um olhar a partir de universitários da cidade de Sinop – MT - Fontes, Gabriela Scroczynski (2014)
This work synthesizes an ethnographic research about the creation e maintenance of social ties by the students from University of Estate of Mato Grosso – UNEMAT, Sinop – MT. The ethnographic method was used in order to perform analytical reconstructions of scenarios and social groups, through dives and observations of the culture of the group studied, looking for clues and characteristics that contribute to the understanding of it. To understand how the college student, from Sinop builds and maintains social ties in both urban space and in cyberspace and how the media and new communication technologies participate in this process, semi-structured interviews were conducted with 13 students, whose ages range 18-33 years. In addition, were also used as instrument of data collection the photoethnografy and the unsystematic and systematic observation, which were registered in a field notebook. Based on theoretical perspectives from authors as Michel Maffesoli and Muniz Sodré and in the idea that community social life and the social ties were constructed by interaction process which occur by communication, this study noted that the social ties, of the students who participated of this research, are made based on two elements: family and study and the communication tools mediated by mobile communication devices are important instruments used for the maintenance of this social ties.